Cancer, other comorbidity, and risk of venous thromboembolism after stroke: a population-based cohort study. Issue 147 (November 2016) - Corraini, Priscila; Ording, Anne Gulbech; Henderson, Victor W.; Szépligeti, Szimonetta; Horváth-Puhó, Erzsébet; Sørensen, Henrik Toft
Abstract: Introduction: The impact of cancer and other comorbidity on the risk of venous thromboembolism (VTE) after stroke is poorly understood. Methods: We used Danish population-based national databases to conduct a cohort study encompassing 201, 025 patients diagnosed with a first-time ischemic stroke, intracerebral hemorrhage, subarachnoid hemorrhage or unspecified stroke between 1995 and 2012. As a comparison cohort, 983, 222 members of the general population were matched to the stroke patients by date of diagnosis, year of birth, sex, and specific comorbidities, using conditions in the Charlson Comorbidity Index and other VTE risk factors. We computed VTE cumulative risks, rates, and rate ratios. We examined the interaction with comorbidity, defined as the excess VTE rates not explained by stroke and comorbidity alone, for up to five years following stroke. Results: Five-year VTE risks were 2.1% and 1.9% in the stroke and comparison cohorts, respectively. Three-month VTE rates peaked at a 5-fold increase (95% confidence interval [CI]: 4.4; 5.2) in stroke patients and remained 13% to 43% increased relative to the general population during subsequent follow-up. During the first three months after stroke, 15% to 33% of the VTE rates were attributable to the interaction between stroke and moderate (2-3) to high (≥ 4) comorbidity based on Charlson Comorbidity Index scores. Non-metastatic solid tumors and metastatic disease accounted for most observed interaction with stroke, representing 41% and 56% of attributable three-month VTE rates, respectively. No such interaction between comorbidity and stroke was observed during subsequent follow-up. Conclusions: Comorbidity, particularly cancer, increased the risk of VTE within three months following stroke. Highlights: After a first-time stroke, the absolute 5-year risk of VTE was 2.1%. Stroke conferred a 5-fold increased risk of VTE within 3 months after diagnosis. Comorbidity, particularly cancer, increased VTE risk up to 3 months after stroke.